Romania Toward a Low Carbon and Climate Resilient Economy : Transport Sector Analysis - World Bank (World Bank, Washington, DC, 2016)
In Romania, as well as in many other East European countries, transport sector Green House Gas (GHG) emissions are increasing fast and their growth is expected to continue into the future, accompanying the on-going economic convergence with the European Union (EU). The objective of the analysis was to assess the impact of green policies and investments on transport emissions. For this purpose, the Romania Transport Strategic Emission Prediction Tool (TRANSEPT) was developed. The outcome of the analysis is a set of proposed green measures, their cost (investment and operational), and their abatement potential. The findings show that Green interventions in Romania lead to a significant reduction of GHG emissions growth as compared with the Baseline and to a gradual decoupling of transport sector emissions growth from economic growth, thus achieving the goal of transport sector mitigation. The main modeling outcomes include abatement potential, cost, and the cost effectiveness (cost per unit of abatement) of the selected green interventions for the period 2015-2050. Financing needs for the recommended measures in transport rise sharply between the Green and the Super Green scenarios, but still remain modest, as incremental investments within a large sector. As the last step of the analysis, a Marginal Abatement Cost Curve (MACC) provided a framework to present the outcomes of the transport sector analysis in a form useful for policy discussions. As Romania’s motorization rate converges with that of the EU, transport emissions are expected to grow even if green measures in the sector are implemented. To conclude, the proposed mitigation action plan recommends a set of actions on the basis of the estimates made in this assessment where institutional arrangement and coordination are also critical.